2022
DOI: 10.1111/nph.18058
|View full text |Cite
|
Sign up to set email alerts
|

Core arbuscular mycorrhizal fungi are predicted by their high abundance–occupancy relationship while host‐specific taxa are rare and geographically structured

Abstract: Habitat restoration may depend on the recovery of plant microbial symbionts such as arbuscular mycorrhizal (AM) fungi, but this requires a better understanding of the rules that govern their community assembly.We examined the interactions of soil and host-associated AM fungal communities between remnant and restored patches of subtropical montane forests.While AM fungal richness did not differ between habitat types, community membership did and was influenced by geography, habitat and host. These differences w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 81 publications
1
5
0
Order By: Relevance
“…While ASVs are likely overestimating AMF species, their d´values for specialization ranged from 0.2 to 0.5 in the roots of the analyzed plant species (Kajihara et al, 2022), i.e., were in a range similar to the values found here. In restored forests, d´was slightlybut significantlylower than in forest remnants (Kajihara et al, 2022), thus, also resembling the effects found here with lower d´(0.2) for ubiquitous AMF taxa and higher d( 0.3) for AMF taxa associated only to forest plants. Since these dv alues are closer to zero (no specialization) than to 1 (specialization) our data agree with the results of metaanalyses that AMF species may have a preference for certain plant communities rather than plant species (Hoeksema et al, 2010;Yang et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…While ASVs are likely overestimating AMF species, their d´values for specialization ranged from 0.2 to 0.5 in the roots of the analyzed plant species (Kajihara et al, 2022), i.e., were in a range similar to the values found here. In restored forests, d´was slightlybut significantlylower than in forest remnants (Kajihara et al, 2022), thus, also resembling the effects found here with lower d´(0.2) for ubiquitous AMF taxa and higher d( 0.3) for AMF taxa associated only to forest plants. Since these dv alues are closer to zero (no specialization) than to 1 (specialization) our data agree with the results of metaanalyses that AMF species may have a preference for certain plant communities rather than plant species (Hoeksema et al, 2010;Yang et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
“…Santos et al, 2006;Torrecillas et al, 2012). For example, a deep sequencing effort of AMF species in roots from five native and one introduced plant species in a remnant and a restored forest on Hawaii resulted in the identification of 1766 amplicon sequencing variants (ASV) (Kajihara et al, 2022). While ASVs are likely overestimating AMF species, their d´values for specialization ranged from 0.2 to 0.5 in the roots of the analyzed plant species (Kajihara et al, 2022), i.e., were in a range similar to the values found here.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations